Pengaruh Influencer Marketing dan Kualitas Produk terhadap Minat Beli Konsumen : (Studi Kasus pada Brand Dricha Skincare) - Asri Wulan Fadillah Sari; Ambardi Ambardi (Kajian Ekonomi dan Akuntansi Terapan, 2025)
Advances in technology and information have given rise to digital innovations such as e-commerce and social media, which have had a major impact on the beauty industry. One popular strategy is influencer marketing, which involves utilizing public figures to influence the purchasing decisions of audiences. In addition, product quality is also an important factor that determines consumer purchasing interest. This study aims to analyze the influence of influencer marketing and product quality on consumer purchasing interest in the Dricha Skincare brand. The method used is a quantitative approach with a survey of 81 respondents selected using the Slovin formula. The data were analyzed using multiple linear regression with tests for normality, multicollinearity, and heteroscedasticity.